If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 6) = 81x Reorder the terms: 3(6 + x) = 81x (6 * 3 + x * 3) = 81x (18 + 3x) = 81x Solving 18 + 3x = 81x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-81x' to each side of the equation. 18 + 3x + -81x = 81x + -81x Combine like terms: 3x + -81x = -78x 18 + -78x = 81x + -81x Combine like terms: 81x + -81x = 0 18 + -78x = 0 Add '-18' to each side of the equation. 18 + -18 + -78x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -78x = 0 + -18 -78x = 0 + -18 Combine like terms: 0 + -18 = -18 -78x = -18 Divide each side by '-78'. x = 0.2307692308 Simplifying x = 0.2307692308
| -540.00+13.5g=4158.00 | | 3r-21=7 | | -540.00+13.5g=1500.00 | | 4x+121=2x+123 | | 6d-10= | | 17(t-3)(t-8)=0 | | 15.4+3.5h=1.2h-6 | | 3.3n+3.4=54+6n | | 12d-84= | | -6+15g=9+15g | | 8y-30=34 | | 3(y+2)=y+24 | | 2x+15=14-x | | (-8x+2y)(-4x+4y)= | | c=(3x+y-4)*5-5y+3 | | 5-15t=-15t-14 | | 4+14x=2x-8+12x | | -18n+6n-3=5-12n | | 965.3616=87.92*r^2+62.17*r | | -6y-1=-9y+2 | | 7x-5+3x=75 | | -6-10v=-10v-6 | | w^2-2w=-67 | | -4m+7=7-4m | | 3(p-3)=24 | | -3z-10=-z+10 | | -8r-9=-8r | | 2(x-3)+5(1-x)=2 | | 11m-66-17= | | 5k-9=-9+5k | | 40(9+7x)+3-5x=17 | | 965.3616=87.92*r^2+6.28*r*9.9 |